Study on Post-Graduation Labor Migration Intentions: A Case Study of University Students in the Mekong Delta, Vietnam - Hong Minh Ngoc Tran (Migration Letters, 2023)
This study aims to explore the factors influencing the labor migration intentions of university students in the Mekong Delta region to provinces and cities in the Southeastern region of Vietnam. This research was conducted by surveying the perspectives of 352 final-year students from various universities situated in three provinces and cities in the Mekong Delta region, namely Can Tho City, An Giang Province, and Kien Giang Province. The results of the Binary Logistic regression model identified six significant factors affecting the labor migration intentions of students in this region. These factors were ranked in decreasing order of impact as follows: Improving the working environment, job stability when migrating, increasing income, family encouragement for labor migration, family economic status, and local climate change. All six of these factors had a positive impact on students’ intentions to engage in labor migration. Among them, the impact of family economic status is noteworthy as it represents a new discovery in this research, indicating a direction of influence that is completely contrary to previous studies on labor migration.